Video Generation using Still Images - Kumar, Neetish; Raj, Deepa (International Journal of Computer Sciences and Engineering, 2025)
A video is termed as the sequence of kinetic frames captured/ play backed into some sequences. The rapid development of video capturing systems changed the word from recording the still frames on tapes to the storing frame digitally through charge coupled devices. The Video recording system changes from past analog era to digital era which made editing and manipulation very easy. This paper explained how Matlab is used for making the video from the still images and its performance in the sense of storage and time. Different video generation tools are elaborated and compared with the Matlab generated tools. Keywords— Matlab, frames, Video generation, Recording systems, CCD